Assessment of Capacity-Building Modules for Students of Electrical Installation Works and Maintenance in Craft Development Centres in Rivers State - Nwiku, Bethel Barinaadaa (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The aim of this study was to assess capacity building module for students of electrical installation works and maintenance in craft development Centres in Rivers State. The study adopted research & development design. The population of the study comprised of 32 teachers and 21 instructors. The entire population was used without sampling because it was considered manageable. Seven research questions were asked and seven null hypotheses were formulated and tested. The instrument used for data collection was a structured questionnaire which was validated by two experts in the Department of Technical Education of the Ignatius Ajuru University of education and Rivers State University respectively. A reliability coefficient of 0.75 was obtained using Cronbach Alpha reliability Coefficient method. The data collected were analyzed using mean and standard deviation, while t-test statistical tool was used to test the hypotheses at 0.05 level of significance. The result of the study shows that the respondents agreed to all the variables but has separate opinion on the last variable (method of evaluation). The researcher found among others, that the existing capacity building module in craft development centres are inadequate and are not uniform across schools in the State. And therefore, recommended among others that Ministry of labour and productivity and similar examination bodies should consider using the newly electrical installation works and maintenance craft module in assessing practical competence of students’ performance again Rivers State government should take over funding of craft development centres to enhance smooth running of program